Attitudes and acceptance of mRNA-based vaccine for neglected tropical diseases: A multi-country study in Asia - Li Ping Wong; Hai Yen Lee; Haridah Alias; Di Khanh Nguyen; Abhishek Lachyan; Farhana Nishat Seheli; Jamil Ahmed; Zhijian Hu; Yulan Lin (Human Vaccines & Immunotherapeutics, 2025)
This study seeks to investigate willingness to receive vaccination against NTDs using mRNA-based vaccines in various Asian countries, including China. Between June and December 2023, an anonymous cross-sectional survey was carried out in five countries. The survey assessed knowledge and attitudes regarding mRNA vaccines and their potential impact on vaccination acceptance. The majority indicated being somewhat willing (44.9%), 19.3% expressed extreme willingness. High knowledge scores (adjusted odds ratio [aOR] = 2.61, 95% confidence interval (CI): 2.31–2.96] were associated with higher willingness to receive mRNA-based NTD vaccines. Participants from Bangladesh recorded the highest proportion expressed willingness (51.4%), followed by China (15.9%). Vietnam (15.4%) and Malaysia (14.8%). Pakistan (11.0%) and India (11.3%) recorded lowest proportions of willingness. Understanding the mechanism of mRNA vaccines and awareness of the difference between mRNA vaccines and conventional ones are knowledge items that significantly predict acceptance. Concerns regarding potential unknown side effects associated with mRNA-based approaches, and the perception that traditional vaccine development methods are safer, negatively correlate with willingness. Conversely, the belief in the advantages of mRNA-based approaches, such as rapid development, heightened potency, and reduced cost, positively correlates with willingness. High overall knowledge and attitudes scores were associated with a higher willingness to receive vaccines. The younger age group and females demonstrated a greater vaccination acceptance. Overall, the study highlights both opportunities and challenges in promoting the uptake of mRNA-based vaccines against NTDs in Asia countries. The study provides insights into enhancing knowledge and fostering positive attitudes toward mRNA-based vaccines.